Between Cult and Spirituality: A Theological Interpretation of Pilgrimage Practices at Sacred Sites in the Nusantara - Nurhanifah; Lila Pelita Hati; Farhan Indra; Ahmad Tamrin Sikumbang; Azhar Sitompul (Pharos Journal of Theology)
This article analyses the practice of pilgrimage to the graves of saints in the Indonesian archipelago from a historical-theological perspective, focusing on its enduring connection to animistic traditions. Originating from pre-Islamic customs such as offering food to ancestral spirits, this practice has been adapted into a localised form of Islam that remains controversial from the standpoint of normative Islamic theology. Employing a qualitative descriptive method, supported by an analysis of relevant Qur’anic verses and classical tafsir, this study reveals that saint veneration, supplications at tombs, and ritual offerings often deviate from the principle of tauhid—the oneness of God. To critically assess these practices, the authors propose the Tauhid-Centric Syncretism Critique as a conceptual framework to evaluate the theological legitimacy of localised religious traditions. This article argues for the need to re theologise such practices to prevent the erosion of Islamic monotheism and to promote a religious identity that is both culturally rooted and theologically sound. The research further explores how pilgrimage in the Southeast Asian context often blurs the line between institutional religious systems (or "cult") and personal spirituality. Rather than dismissing the cultural richness of local traditions, the study urges for a critical and theological filtering process to distinguish between permissible cultural expression and syncretistic distortions. In doing so, the article contributes to the discourse on Islam, culture, and theology in the Nusantara by offering a balanced perspective that upholds the integrity of tauhid while acknowledging the complex dynamics of religious acculturation.